Thermally stable P-chiral supramolecular phosphines, their self-assembly and implication in Rh-catalyzed asymmetric hydrogenation - Chandanshive, Amol C.; Gonnade, Rajesh G.; Chikkali, Samir H. (Chemistry-A European Journal, 2024)
P-chiral supramolecular phosphine ligands are crucial for asymmetric transformations, but their synthesis is tedious. We report a one-step synthesis of thermally stable P-chiral supramolecular phosphines and their performance in the asymmetric hydrogenation of functionalized alkenes. A rational designing and synthesis of (R, R)-QuinoxP* ligated palladium complex (Pd-2) in excellent yield is reported. This Pd-2 catalyzed a direct P-C coupling of 2,3-dihydro-1-H-phosphindole (A1)/1,2,3,4-tetrahydrophosphindoline (A2) with 1-(3-iodophenyl)urea (B1)/2-iodo /6-hydroxy pyridine (B2) and,produced corresponding ligands L1-L3. The P-C coupling between A1 and B2 produced 6-(2,3-dihydro-1H-phosphindol-1-yl)pyridine-2(1H)-one (L2) with an excellent enantiomeric excess of up to 99 %. L2 was found to be remarkably stable even at 150 degrees C and did not oxidize/hydrolyze for at least 24 hours in open air. Such thermal stability and an impediment to oxidation are unprecedented. L2 self-assembled and produced L2-C1 (Pt), L2-C2(Pd), and L2-C3(Rh) assemblies. The utility of the self-assembled P-chiral ligand was demonstrated in the Rh-catalyzed asymmetric hydrogenation (AH) of functionalized olefins. The L2-C3 catalyzed AH of functionalized alkenes and delivered chiral products with excellent enantioselectivity of >99 %. A small library of 16 substrates was subjected to AH using L2-C3 to produce chiral compounds with excellent conversion and ee.
Keywords: asymmetric hydrogenation; Asymmetric phosphination; P-chiral phosphine; Self-assembly; Supramolecular phosphine